Child’s Struggle To Survive In Ma’mun Affany’s Novel Do’a Anak Jalanan - Muhammad Tahir (CERED Indonesia Institute, 2021)
According to the Ministry of Social Affairs, “Street children are child who spends most of his time to perform activities of daily living on the streets, either for a living or wandering the streets and other public places. street children discrete, aged between 5 to 18 years, doing activities or roaming the streets, mostly dull appearance neglected and clothes, high mobility”. This study was conducted by using descriptive qualitative method has the meaning that the writer will explain the result of analysis in the form of words and sentence since the result is not numeral data. Roberts (1999: 45). The findings of this study show that, Dina, Adib, and Cindy are three children born to either of whose womb but must live together as one under the auspices of the squeeze sweat every day. They are aware of life lived unworthy, they want to continue to reach the goal to be the school that no longer roam the streets despite slur, should blow them feel. Three of them continue to hold up, continue to live life, keep fighting, keep trying, because they believe the struggle is far better than having to die despite sore vain.